So Deeply Embedded: Using Inquiry to Understand the Influence of Popular Media in the Classroom - Christa Boske; Susan McCormack (Educational Considerations, 2008)
This inquiry originated with discussions among a group of colleagues’ after viewing Happy Feet, a Warner Brothers film released in November 2006. This film, like many other animated films aimed at preschool and school-aged children, contained hidden messages.
Keywords: educators; preservice teachers; school; leaders; popular media; critical inquiry; universities; literacy